ROLE OF CHITOSAN, CARBOXY METHYL CELLULOS, POLYVINYL PYRROLIDONE, KYRON T134 AND PRIMOGEL TO DESIGN THE MOUTH DISINTEGRATING TELMISARTAN TABLET WITH EXTENDED RELEASE PROFILE - Akram, Muhammad Abdullah; Taha, Nida; Nazir, Taha (INDONESIAN JOURNAL OF PHARMACY, 2017)
The Mouth Disintegrating Extended Release Telmisartan (MDERT) tablets are designed for adequate pharmacokinetic profile to avoid the unusual peaks and troughs. Although, there are extensive advance techniques used to deliver drugs. But oral route is still remains effective in most of the therapeutical situations. Thus we aimed this study to formulate a dosage form with dual character of orodispersion as well as extended effectiveness. MDERTS dosage form was prepared by direct compression method. The major components of this preparation were Telmisartan (TLM), Carboxy methyl cellulose polyvinyl Pyrrolidone, Chitosan, Talc, Mg-stearate, Lactose. The MDERTS dosage form was characterized with different determinants. While, the drug release curves of all 6 formulations upto 12h, DSC spectra of TLM, Kyron T134, Primogel, TLM+Kyron T134+Primogel, Chitosan, CMC and different excepients are presented as comprehensive scientific figures. DSC and FTIR spectroscopic studies indicate the compatibility of drugs with each other and with excipients. Moreover, the formulation F2 containing more than 10% of Kyron T had shown best results. Whereas, the overall results had shown that Kyron T containing tablets had best, in vitro dispersion time, wetting time and wetting volume, water absorption ratio. The order in which superdisintegrants and polymers had produced desirable effect is Kyron T134 > KyronÂ  T134134 + primogel > primogel and for polymers chitosan> chitosan+CMC> chitosan +PVP> CMC> CMC+PVP> PVP. Thus, Kyron T is the best superdisintegrant of others which were used in present study and direct compression method is the best used to prepare extended release mouth disintegrating tablets.Â Â